2015
DOI: 10.1093/gji/ggv221
|View full text |Cite
|
Sign up to set email alerts
|

Sources of secondary microseisms in the Indian Ocean

Abstract: S U M M A R YOcean waves activity is a major source of microvibrations that travel through the solid Earth, known as microseismic noise and recorded worldwide by broadband seismometers. Analysis of microseismic noise in continuous seismic records can be used to investigate noise sources in the oceans such as storms, and their variations in space and time, making possible the regional and global-scale monitoring of the wave climate. In order to complete the knowledge of the Atlantic and Pacific oceans microseis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 48 publications
(65 reference statements)
4
24
0
Order By: Relevance
“…As already observed for secondary microseisms (e.g. Koper & de Foy 2008;Stutzmann et al 2012;Davy et al 2015), the sources around India experience a strong seasonality typical of the southern hemisphere.…”
Section: Seasonal Variationssupporting
confidence: 65%
“…As already observed for secondary microseisms (e.g. Koper & de Foy 2008;Stutzmann et al 2012;Davy et al 2015), the sources around India experience a strong seasonality typical of the southern hemisphere.…”
Section: Seasonal Variationssupporting
confidence: 65%
“…In this case, the SM increase recorded on the island can be considered as a warning and precursor of the swell generated by the storm, which takes usually about 3-4 d to propagate northeastwards before reaching La Réunion Island. The source of this noise is located in the southern Ocean, as demonstrated by Davy et al (2015) from the analysis of permanent seismic stations located in the Indian Ocean and also modelled from wave dynamics (Ardhuin et al 2011;. This particular swell event was recently analysed at the seismic stations located in the Mozambique channels (Barruol et al 2016) and the map of this swell propagation in the SW Indian Ocean was presented in their Fig.…”
Section: Austral Swell-related Seismic Noise Recorded By a Seismologimentioning
confidence: 95%
“…SM noise sources have been located in near-coastal shallow waters, related to coastal swell reflection with the incident swell (Bromirski & Duennebier 2002;Bromirski et al 2013), but also in deep waters, related to interactions between swells from two distinct storms Beucler et al 2014). For the Indian Ocean, it has been recently shown that the dominant SM sources are located at large latitudes in the south of the ocean basin, associated with large atmospheric low-pressure systems moving from west to east around Antarctica (Davy et al 2015), but also that SM can be generated by major tropical storms occurring at intermediate latitudes in tropical regions (Davy et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The SFMs are generally believed to be generated by the direct impact of ocean waves on the ocean floor (Ardhuin et al, ; Barruol et al, ; Cessaro, ; Hasselmann, ), while the DFMs require the interaction of opposing wavefields that have nearly the same wave number, which generates a pressure excitation pulse at twice the wave frequency acting on the ocean floor (e.g., Ardhuin et al, ; Bromirski et al, ). Although the causal mechanisms of SFMs and DFMs are well accepted, their source locations and wave types are still under investigation, and an unified theory explaining all the observations has not been achieved yet (Behr et al, ; Chen et al, ; Chevrot et al, ; Davy et al, ; Diez et al, ; Gerstoft & Tanimoto, ; Gualtieri et al, ; Landes et al, ; Möllhoff & Bean, ; Nishida et al, ; Obrebski et al, ; Reading et al, ; Sergeant et al, ; Sufri et al, ).…”
Section: Introductionmentioning
confidence: 99%